Association of HLA (Class I & II) and Susceptibility to Hydatid Cyst Disease - Al-Joofy, Ikbal Kh.; Mahmoud, Mohanad H.; Maki, Amal M.; Omar, Amera J.; Shareef, Salwa M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Hydatid cyst disease is a parasitic zoonotic disease caused by genus Echinococcus. This disease believed to has genetic background in it’s aetiopathogenesis course . The aim of this study is to shed light on the possible correlation between HLA-class I (A,B,C) & HLA-class II (DR & DQ) antigens and the susceptibility to this disease. Patients & Methods: Fifty patient with hydatid cyst disease before undergoing surgical operation were investigated for HLA. Class I and class II by using microlymphocytotoxicity test. The results were compared with 115 healthy control. Results: Significant increased trend of HLA-A28 and A-11, -B18 and B-35, -DR3 and DR-11 (P<0.001, P<0.01) in patients with this disease as compared with healthy control. On the other hand, increased trend of HLA-28 (P<0.01) in patients with hydatid disease especially in those with a cyst location in liver. Conclusions: High frequency of HLA-A11 and –A28, B18 and –B35, -DR3 and –DR11 antigens may play major role in susceptibility to hydatid disease. HLA-A28 could be the most related antigen to this disease and acting as genetic marker that could in one way or another play crucial role in susceptibility especially in cases of hydatid disease in liver.